The Strategy for Preparation of Educational Research Proposal for Students of PGSD UNU Sumbar Program - Nofriza Efendi; Yona Syaida Oktira; Kristian Burhan; Gingga Prananda (The Future of Education Journal, 2023)
Research is channeling human curiosity about a problem by using certain treatments such as examining, investigating, studying and studying carefully and formulating hypotheses on a problem so that an achievement of correct answers to problems is obtained, development of science and so on. The purpose of this study is to see how the strategy for preparing educational research proposals for PGSD study program students is. This type of research is a literature study from several previous services. This webinar activity received a good response from the public and enthusiastic participants. With this activity students are able to write and make educational research proposals according to the steps and strategies that have been understood and can be applied properly and correctly